Discontinuous low temperature stress and plant growth regulators during the germination period promote roots growth in alfalfa (Medicago sativa L.) - Jiang, Gaoqian (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.